Contribution of child maintenance on lone mothers' income in five welfare states - Mia Hakovirta; Merita Jokela (Luxembourg Income Study (LIS), 2018)
This study uses the Luxembourg Income Study (LIS data) from 2013 to study 1) the contribution of child maintenance to the income packages of lone mothers, 2) the proportion of lone mothers receiving child maintenance and the level of child maintenance for those receiving it, and 3) the extent to which child maintenance is helping families that may need it the most (those at the low end of the income distribution), compared with families with moderate or higher incomes. Our analysis covers data from five countries: Finland, Germany, Spain, UK and the USA. Our results show that in all countries except the UK, labour income is an important source of income for lone mothers and less than 40 percent of income comes from social transfers. Child maintenance contributes significantly to the income of lone mothers, particularly in Spain, followed by the USA and Germany. We find the highest coverage of child maintenance receipt in Finland. In the other countries, only one third of lone mother households receive child maintenance. The median amounts of maintenance are the lowest in the UK and Finland but there is great variation in the level of child maintenance within countries. The comparison of the quintile groups reveals that in the USA the lone mothers in lowest income quintile do not seem to benefit as much from child maintenance compared with the highest income quintiles, whereas in Finland, Germany and Spain more lone mothers in the low-income quintiles receive maintenance. However, amounts are quite equal across income quintiles.
Keywords: 330; child maintenance; child support; income package; comparative study; lone mothers